Cost analysis of magnetically controlled growing rods compared with traditional growing rods for early-onset scoliosis in the US: an integrated health care delivery system perspective - Polly, David W (Clinicoecon Outcomes Res, 2016)
PURPOSE: Traditional growing rod (TGR) for early-onset scoliosis (EOS) is effective but requires repeated invasive surgical lengthenings under general anesthesia. Magnetically controlled growing rod (MCGR) is lengthened noninvasively using a hand-held magnetic external remote controller in a physician office; however, the MCGR implant is expensive, and the cumulative cost savings have not been well studied. We compared direct medical costs of MCGR and TGR for EOS from the US integrated health care delivery system perspective. We hypothesized that over time, the MCGR implant cost will be offset by eliminating repeated TGR surgical lengthenings. METHODS: For both TGR and MCGR, the economic model estimated the cumulative costs for initial implantation, lengthenings, revisions due to device failure, surgical-site infections, device exchanges (at 3.8 years), and final fusion, over a 6-year episode of care. Model parameters were estimated from published literature, a multicenter EOS database of US institutions, and interviews. Costs were discounted at 3.0% annually and represent 2015 US dollars. RESULTS: Of 1,000 simulated patients over 6 years, MCGR was associated with an estimated 270 fewer deep surgical-site infections and 197 fewer revisions due to device failure compared with TGR. MCGR was projected to cost an additional $61 per patient over the 6-year episode of care compared with TGR. Sensitivity analyses indicated that the results were sensitive to changes in the percentage of MCGR dual rod use, months between TGR lengthenings, percentage of hospital inpatient (vs outpatient) TGR lengthenings, and MCGR implant cost. CONCLUSION: Cost neutrality of MCGR to TGR was achieved over the 6-year episode of care by eliminating repeated TGR surgical lengthenings. To our knowledge, this is the first cost analysis comparing MCGR to TGR – from the US provider perspective – which demonstrates the efficient provision of care with MCGR.